Production and decomposition rate of leaf litter in areas under rehabilitation in El Porvenir, Hidalgo, Mexico - García-Osorio, María Tonatzín; Plascencia-Escalante, Francisca O.; Ángeles-Pérez, Gregorio; Montoya-Reyes, Francisco; Beltrán-Rodríguez, Leonardo (Instituto de Ecología, A.C., 2020)
The leaf litter from trees is the main route of entry of organic matter and its subsequent decomposition allows the flow of nutrients in the ecosystem. The study of these processes in ecosystems under rehabilitation is of vital importance to determine how such actions are influencing their recovery. This study was carried out to determine the effect of reforestations on litter production and decomposition at El Porvenir, Hidalgo State, México. We selected four different conditions: three correspond to areas with different reforestation ages, 5, 12 and 14-year-old (R5, R12 and R14) while the fourth is a reference site (SR) with remnants of natural vegetation. For each condition, 10 sampling points were selected in which litter traps were placed to quantify the litter production for one year. In 4 sampling points per condition we placed litter bags to measure the rate of decomposition for a 12-month period. The reforestation age showed a positive effect of litter production. The largest litter production was recorded in R14 (0.3099 kg m-2 year-1) while the lowest was for R5 (0.0436 kg m-2 yr-1). The highest and lowest decomposition rates correspond to SR (k= 0.676) and R14 (k = 0.229). On the other hand, the increased release of C was presented in SR and the lowest in R12. For its part, the release of more N at the end of the incubation period was recorded in SR and the lowest in R14.